2020
DOI: 10.3390/agriculture10010012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Affects the Root Development of Strawberry During Plug Transplant Production

Abstract: Hydrogen sulfide (H2S) is endogenously produced in plant cells and plays an essential role in root development. Given its potential for future agricultural applications, the optimal concentration of sodium hydrosulfide (NaHS, an H2S donor) and the potential mechanisms for root development in the strawberry ‘Seolhyang’ were investigated in this study. The results showed that NaHS with a concentration of 1.250 mM had a positive effect on root development in strawberry. Further experiments showed that exogenous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In the previous experiments of our group, Arabidopsis grown on 1/2 MS medium supplemented with 10 ~ 100 μmol/L NaHS had longer roots than the control, while NaHS at concentrations over 200 μmol/L inhibited root elongation, and even suspended root elongation when the concentration exceeded 2 mmol/L. Exogenous application of low concentrations NaHS was found to promote the activity of l -CDes in root cells (Fang et al 2014c ; Hu et al 2020a ), thus, increasing the content of endogenous H 2 S, which would directly promote the development and growth of roots. The same phenomenon was also observed in strawberry seedlings (Hu et al 2020a ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 88%
See 1 more Smart Citation
“…In the previous experiments of our group, Arabidopsis grown on 1/2 MS medium supplemented with 10 ~ 100 μmol/L NaHS had longer roots than the control, while NaHS at concentrations over 200 μmol/L inhibited root elongation, and even suspended root elongation when the concentration exceeded 2 mmol/L. Exogenous application of low concentrations NaHS was found to promote the activity of l -CDes in root cells (Fang et al 2014c ; Hu et al 2020a ), thus, increasing the content of endogenous H 2 S, which would directly promote the development and growth of roots. The same phenomenon was also observed in strawberry seedlings (Hu et al 2020a ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 88%
“…Exogenous application of low concentrations NaHS was found to promote the activity of l -CDes in root cells (Fang et al 2014c ; Hu et al 2020a ), thus, increasing the content of endogenous H 2 S, which would directly promote the development and growth of roots. The same phenomenon was also observed in strawberry seedlings (Hu et al 2020a ). Specific fluorescent probe WSP-1 was applied to track endogenous H 2 S in tomato roots in site, and the results further confirmed that H 2 S accumulation is associated with primordium initiation and lateral root emergence (Li et al 2014c ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…Sadiq et al (2017) also indicated a similar impact of drought on sugars accumulation. Likewise, Hu et al (2020) also found substantial accretion in the total soluble sugars accumulation in strawberry plants pretreated with H 2 S during plug transplantation. The increase in soluble sugars accumulation was due to H 2 S‐induced up‐regulation of sugar biosynthesis genes such as trehalose‐6‐bisphosphatase, sucrose phosphate synthase, and trehalose‐6‐phosphate synthase under drought (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Then, they can be cultivated until transplantation. Recently, study was also focused on the improvement of root development during cutting propagation of strawberry, which suggested that hydrogen sulfide could promote the root development (Hu et al, 2020). Although cutting propagation consumes less time and labor, the growth, fruit productivity, and fruit quality of strawberry as affected by these two propagation methods have not been investigated.…”
Section: Introductionmentioning
confidence: 99%